PENGARUH MANAJEMEN KELAS DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SD NEGERI DI KECAMATAN WALED KABUPATEN CIREBON - Widiawati, Hema (Jurnal Pendidikan Dasar, 2019)
This research have a purpose for knowing the effect of classroom management and motivation of learning on the students' critical thinking skills in science subjects in class V SDN of Waled Cirebon. The research sample was in class V of SDN Waled as many as 100 respondents taken by the Cluster Sampling Area technique. In this study, we can conclude that there is a direct influence of the classroom management for the critical thinking of 0,603, there is a direct influence of motivation of learners to the critical thinking of 0,786, and there is a direct influence of the classroom management on motivation to learners at 0.536